Transforming Coastal Livelihoods: A Multi-Dimensional Approach to Fishermen’s Empowerment in Pesisir Selatan, Indonesia - Fitri Eriyanti; Zikri Alhadi; Iip Permana; Yuliarti Yuliarti; Artha Dini Akmal; Rahmadani Yusran (Asosiasi Ilmuwan Administrasi Negara (AsIAN), 2025)
Fishing communities in Indonesia continue to face structural challenges such as weak institutions, limited technical capacity, and restricted market access. This study analyzes a community empowerment program implemented through institutional strengthening, skills development, and digital marketing in the Bunda Saiyo Culinary Tourism Group in Pesisir Selatan Regency. Using a qualitative descriptive approach, data were collected through in-depth interviews, observations, and document reviews. The results indicate notable progress in four key dimensions: (1) institutional strengthening, evidenced by a clearer organizational structure and increased member participation (up by 65%); (2) technical skills, reflected in a 45% increase in product diversification and improved quality standards; (3) marketing, through the adoption of digital platforms that expanded market reach by approximately 40%; and (4) entrepreneurship, demonstrated by members’ higher initiative and the creation of new business ideas. These changes have contributed to an estimated 35–50% rise in monthly turnover and enhanced household income stability. However, limited access to capital and lingering pandemic effects remain constraints. The findings highlight that sustainable empowerment of fishing groups requires an integrated, multi-dimensional strategy combining institutional, technical, and market-based interventions.